Genetic variability and correlation in onion (Allium cepa) - Singh, D N; Nandi, A; Tripathi, P; Sahu, A (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during thc winter season of 1990-93 to study genetic variability and correlation in 9cultivars (’Nasik Red’, ’N 53’, ’VL 1’, ’VL 3’, ’Multiplier’, ’Bombay White’, ’Bombay Red’, ’Gujarat White’ and ’Puna Red’)of onion (Allium cepa L.). Bulb weight, bulb yield/ha and dry leaves/plant had high genotypic coefficient of variation(21.95, 20.72 and 20.28 respectively), heritability (97.88, 96.95 and 95.92% respectively) and genetic advance (44.80, 42.05and 40.96% respectively). Bulb yield showed strong positive correlation with bulb weight and neck girth.